IMPROVING THE EFFICIENCY OF BRIQUETTE PRODUCTION THROUGH DRYING OF COAL DUST - Nasiba Vokhidova (Modern American Journals, 2025)
This article investigates the kinetics of coal fines drying in a contact drum apparatus equipped with a rapidly rotating rotor. The study focuses on the experimental determination of the drying curve and the drying rate curve, which are essential for characterizing the moisture removal process of fine coal particles. The methodology involves monitoring temperature and moisture content variations during contact drying, followed by the calculation of drying rates at different process stages. Based on general theoretical principles of drying and its governing laws, a detailed physical picture of the drying process is presented, including the periods of constant and falling drying rates. Special attention is given to the influence of particle size, initial moisture content, and contact conditions on the overall drying efficiency. The results provide a clearer understanding of heat and mass transfer mechanisms in contact drum drying, offering practical recommendations for optimizing briquette production through more energy-efficient and uniform drying of coal fines.
Keywords: Drying kinetics, drying rates, drying rate curve, coal fines, contact drying, briquette production efficiency.